الحماية الدولية من الاعتداء على البعثات الدبلوماسية اثناء النزاعات المسلحة ‏في ليبيا - شبشوبي، عبير المبروك عبد الله (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2018)
Today's world is looking for security and has not reached it, as the political ‎and economic crisis are still present strongly, which led to the expansion of ‎the imposition of security measures in excess of all expectations, which ‎emphasizes the importance of the international protection of diplomatic ‎missions during armed conflicts and during the attempt of the state to ‎appear as a holding state. The importance of this study, which is the ‎manifestation of some of the problems faced by the diplomatic envoy in ‎Libya following the Libyan revolution (February 2011) and with the aim of ‎achieving the objectives of the study has been used the historical approach ‎‎(the history of the Libyan diplomacy) and descriptive approach, which is to ‎describe the phenomenon and study the relationship between what is in ‎real situation and some of the previous events which have been influenced ‎or muffled in the previous events and current circumstances. The study ‎concluded that the responsibility for the international protection of ‎diplomatic missions during armed conflicts is a double responsibility, and ‎the evidence is that the diplomatic envoy at this stage is protected under the ‎‎1961 Vienna Convention on International Relations and the 1949 Geneva ‎Convention. The study concluded that it is not related to the legislative ‎texts as much as it is related to the necessity of activating the security services ‎and the national judiciary, and raising the capabilities and skills of the ‎concerned parties to save the law and prosecute the perpetrators and impose ‎sanctions on them.